To What Extent Does Informal Digital Learning of English Contribute to Learners’ Communicative Competence? - Nugroho, Arif; Van, Dao Thi Hong; Putra, Heldi Ramadhan; Nanda, Giswa Aria (Universitas Islam Negeri Raden Intan Lampung, 2022)
The increase accessibility of online resources in day-to-day communication in the digital era offers ample opportunities for informal language learning to enhance learners’ communicative competence. Addressing the issue, this sequential explanatory study sheds some light on the empirical relationship between informal digital learning of English (IDLE) activities and the development of learners’ communicative competence. Moreover, the types of IDLE activities are further depicted. A web-based survey and semi-structured interviews were employed to elicit the required data from 279 Indonesian undergraduate learners majoring in English education and linguistic studies. Drawing on a multiple linear regression analysis, the results depicted that both receptive IDLE activity (e.g. listening to English music online) and productive IDLE activity (e.g. chatting in English with others) contributed to the enhancement of the learners’ communicative competence. The semi-structured interviews further portrayed several types of IDLE activities which have fruitful insights for the learners’ communicative development. This study concerns on the current phenomenon of how language learners are exposed to the present-day technological advancement in a range of informal learning environments, along with some didactic implications for English language teaching.